An ethnographic discourse approach to explore GP-counsellor communication in primary health care settings in Hong Kong - Pun, Jack; Yu, Qianwen Joyce; Lee, Matthew K. C. (Frontiers in Psychology, 2022)
This study aims to explore the nature of GP-counsellor interaction during discussions of patients’ mental health issues in primary care services. An ethnographic discourse analysis of audio-recorded GP-counsellor conversations and the participating counsellor’s reflective accounts. Two participating GPs and one counsellor were recruited from a private medical clinic in Hong Kong. The GPs and the counsellor mainly discussed their patients’ issues in terms of medication management, the counsellor’s case conceptualization, the case management, knowledge transfer and acknowledging the partnership. During case discussions, both the GPs and the counsellor used a range of interactional strategies to clarify a patient’s condition and treatment plans for mutual understanding. The GPs and the counsellor co-construct an insider discourse that covers a greater diversity of topics, including both medical and non-medical concerns. The research findings have implications for theory and practice, including the potential of ethnographic discourse analysis in understanding the features of participants’ behavior and evaluating the effectiveness of communication in a particular setting, as well as the importance of exploring professionalized discourse during GP-counsellor communication in developing training programs aimed at enhancing staff awareness of effective IPC communication.